Wild horses - Oldfield, Jenny (Hodder Children's London, 1999)
Kirsty and her pony become separated from their trekking group and are trapped in Dead Man's Canyon - Here she finds a herd of wild horses, one of whom has been injured by falling rocks - In the face of a gathering storm, Kirsty resolves to get help for the injured stallion______________